PEMERIKSAAN STATUS GIZI ANAK DI POSYANDU DESA TANGGUNG KECAMATAN TUREN KABUPATEN MALANG - Riskiyah, Riskiyah; Rokhiyah, Rozibatul; Yogi, MUhammad; Fitriani, Desi; Mar’atur, Novia; Khabibah, Hanik; Dakhilullah, Muhammad; Rosyida, Nafissatur; Fadhil, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Nutrition is one of the determinants of the quality of human resources who are qualified, intelligent, healthy, and productive Continuous monitoring of the nutritional status of children is essential for the early detection of children with dietary problems. One way to monitor a child's growth is to screen for nutritional status. The purpose of this service activity is that KKM group 170 can participate in Posyandu activities and assist in carrying out healthy status checks to determine the nutritional status of children in the village of Responsibility. The method of examining the nutritional status of children is by measuring their weight and height. Some measure weight using dacin or stepping scales while measuring height using a length board or microtoise. Thirty-four children came to this Posyandu. The results of this service related to the examination of the nutritional status of children found that the majority who came to Posyandu were 20 men and 14 girls. For nutritional status, the majority are well nourished 79.42%, at risk of nutrition 2.94%, Obesity 5.88%, Overnutrition 2.94%, Undernutrition 5,88%, and suffering from malnutrition 2.94%.